MENINGKATAN KREATIVITAS BELAJAR IPA MENGGUNAKAN MODEL PROJECT BASED LEARNING (PjBL) BERBASIS DARING MATERI SISTEM EKSKRESI PADA KELAS VIII-6 DI MTs NEGERI 31 JAKARTA - Wahyuni, Nanik (JOEL: Journal of Educational and Language Research, 2021)
Science learning in Madrasas was developed as an integrative science subject, not as an educational discipline. Both are applicative-oriented education, developing thinking skills, learning abilities, curiosity, and developing caring and responsible attitudes towards the natural and social environment. Integrative science has the meaning of combining various aspects, namely the domain of attitudes, knowledge, and skills. The problem of the lack of student creativity in science learning, of course, must immediately take action so that students become creative in learning and can be improved as expected. Therefore, to increase student creativity in the midst of a pandemic, researchers can provide learning innovations. One of the innovations that can be provided in the learning process is applying the learning model. One of the learning models that can increase creativity is the project based learning (PjBL) model or project-based learning. The research method used in this study is the CAR method consisting of a series of four activities carried out in an iterative cycle (Kemmis and Taggart, 1988). The four main activities in each cycle are planning, acting, observing and reflecting. The results of the study showed that the average score of 35 students in the first cycle was 70.71. Students who scored less than the KKM were 11 students (31.43%), while students who scored above the KKM were 24 students (68.57%). The average value of 35 students in the second cycle was 77.60. Students who scored less than KKM were 8 students (22.86%), while students who scored above KKM were 27 students (77.14%). There was an increase of 6.89%, this indicates that the indicators of success were achieved. So this research is only up to cycle II. The implementation of creativity showed by the teacher in the first cycle of 76.47% and the second cycle of 97.12%. The implementation of the online-based project based learning model showed that the students in the first cycle were 71.31% and the second cycle was 86.18%. There was an increase in creativity in learning science using an online-based project based learning (PjBL) model, especially the excretory system material